The usage of data in NHS primary care commissioning: a realist synthesis and evaluation - Jager, A (2023)
Against a backdrop of a rapidly ageing population facing increasingly complex health challenges, policy-makers have encouraged primary care commissioners in the NHS to increase the usage of data (a form of evidence that can be expressed in numbers) to inform commissioning decisions, i.e. to conduct evidence-based commissioning. The purported benefits of doing so are vast, including the achievement of cost savings as well as improved population health outcomes. However, the limited existing research on evidence-based commissioning has emphasised the complicated and complex contexts commissioners work in and argued that closer attention should be paid to the role of context in facilitating and inhibiting the usage of evidence. The aim of this thesis was to use realist approaches, which have an explanatory rather than a judgemental focus, aiming to understand how, why, for whom, to what extent and in what circumstance interventions and programmes work. My research objectives were to understand: (1) How and why do commissioners use data to inform commissioning, and what outcomes does this lead to? (2) What factors or contexts promote and inhibit their usage of data in commissioning decisions? I used a multimethod qualitative approach, drawing on three sources of secondary and primary data, namely a realist synthesis (systematic review), interviews with commissioners and academic experts on commissioning, as well as recordings of primary care commissioning meetings. I employed an iterative convergent (concurrent) approach to allow the evidence from these three sources to ‘talk to each other’ during the analysis phase, meaning the findings from the three sources were compared and considered, ultimately forming a set of consolidated configurations about how commissioners used data, and the contexts that promoted and inhibited this. These findings were grouped into four conceptual categories related to commonalities across the contexts impacting how commissioners used (or were prevented from using) data: (1) steps of the commissioning cycle, (2) characteristics of data, (3) commissioners’ capabilities, roles, perceptions, and intentions, and (4) commissioners’ relationships with external providers of data (analysis). The novelty of this DPhil lies in its exclusive focus on one form of evidence (data) in the process of primary care commissioning, the application of a realist lens to analyse this, as well as the amount of secondary and primary data gathered and analysed. I found that commissioners use data not only as a form of evidence to inform commissioning decisions, but also as a tool to stimulate commissioning improvements, and as a warrant for convincing others about decisions they wish to make. However, despite being well-intentioned users of data, commissioners face considerable challenges when trying to use them. Commissioners have developed a range of strategies to deal with ‘imperfect’ data, but there are still considerable barriers that inhibit data from being used in certain contexts. Understanding and addressing these will be key in light of the government’s ongoing commitments to using data to inform policy-making, as well as increasing integrated commissioning.